Pax5 Re-expression in H460 Cells Treated with the Combination of Demethylating Agent and Histone Deacetylase Inhibitor is Associated with the Enhancement of P53 Binding to Pax5 Promoter Region - Liang, Yuanxin; Zeng, Jinwu; Jelicks, Linda; Ma, Shengwei; Liu, Jing; Mei, Jingsong; Perez-Soler, Roman; Zou, Yiyu (Current Cancer Drug Targets, 2017)
Background: The epigenetic combinations of DNA demethylating agents and histone deacetylase (HDAC) inhibitors have demonstrated clinical benefits for non-small cell lung cancer (NSCLC) treatment, however, there are few studies uncovering the underlying molecular mechanism of the combinations. Our previous study showed that DNA demethylating agent Azacitidine (Aza) demethylated CpG sites in paired box gene 5 (pax5) promoter region, but did not induce pax5 mRNA or protein expression. Methods: In this study we used epigenetic combination of Aza and HDAC inhibitor Vorinostat (SAHA) to treat NSCLC cells and to elucidate the underlying molecular mechanism. We treated pax5- silenced NSCLC H460 cells with Aza+SAHA combination at sub-toxic concentration and detected the re-expression of pax5 mNRA and protein. Results: The results showed demethylation of CpG sites in pax5 promoter region by Aza treatment and increased DNA accessibility for protein binding by SAHA treatment. The combination of Aza+SAHA significantly increased p53 protein binding to DNA in pax5 promoter region (p<0.01). More efficient binding of the transcription factor p53 to pax5 promoter region is likely because SAHA increased accessibility of the chromatin conformation and Aza-demethylated DNA was more permissive, allowing transcription factors to bind. Conclusion: Our study not only explained an underlying mechanism, that pax5 re-expression was induced by Aza+SAHA combination in H460 cells via p53, but also demonstrated a pattern showing that the combination of demethylating agent and HDAC inhibitor can re-activate tumor suppressor gene (TSG) which is associated with the enhancement of transcription factors binding to the promoter region of the TSG.
Keywords: HDAC